Population density, multiple harvesting, and ability of Ipomoea reptans to compete with native weeds at tropical wetlands - Benyamin Lakitan; KARTIKA KARTIKA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lakitan B, Kartika K. 2020. Population density, multiple harvesting, and ability of Ipomoea reptans to compete with native weeds at tropical wetlands. Biodiversitas 21: 4376-4383. Despite as a nutritious, fast-growing, and well-adapted leafy vegetable at tropical wetlands; Ipomoea reptans has not been intensively cultivated yet. This study was designed for increasing productivity of this vegetable by optimizing population density, extending harvesting period, and its ability to compete with native weeds at tropical wetlands. Bottom wet culture system (BWCS) was implemented by placing all pots within 2 m x 4 m experimental pool filled with water to 2-cm depth to make sure bottom part of the substrate within each pot was continuously water-saturated. Results of this study indicated that despite fluctuated yield at each harvest, accumulative yields after five consecutive harvests were not significantly different among population densities from 14 to 71 plants per m2. Yet, quality of yield in most cases was better in lower population density treatment (14 plants per m2), as indicated by SPAD value and marketable size of individual plants. Frequent NPK fertilizer application was effective for increasing yield. The first harvest was done at 4 weeks after seed sowing; thereafter, the plants were routinely re-harvested at about every week. This fast-growing vegetable also exhibited ability to compete with native weeds commonly found at tropical wetlands at density up to 11.3 mg cm-2.